Overview of immunology of oral squamous cell carcinoma - Anisha Cynthia Sathiyasekar; Pavithra Chandrasekar; Arul Pakash; K U Goma Kumar; M S Jaishlal (Wolters Kluwer Medknow Publications, 2016)
Oral squamous cell carcinoma (OSCC) is the sixth most common malignancy and is a major cause of cancer morbidity and mortality worldwide. Every year, approximately 500,000 new cases of oral and pharyngeal cancers are diagnosed worldwide, and a majority of these cases are seen in developing countries. OSCC arises as a result of multiple molecular events that develop from the combined influences of an individual's genetic predisposition and exposure to environmental carcinogens. Here, we discuss the course of immunological development involving OSCC. We have reviewed a literature available in Medline and Google databases. We draw attention to possible shortcomings and issues requiring clarification. Emphasis is given to precise immunology involving the OSCC. In this article, we try to approach the immunology of OSCC through a practical approach consideration of common difficulties and dilemmas faced by the oral pathologist, and where possible, we offer guidance and practical tips. The article concludes with a brief consideration of the prognostic value of immunology involving the OSCC.